2017
DOI: 10.14744/anatoljcardiol.2017.7452
|View full text |Cite
|
Sign up to set email alerts
|

Urban and rural differences in hypertension risk factors in Turkey

Abstract: Objective:Existing literature shows considerable regional differences in terms of hypertension (HT) prevalence in Turkey. The purpose of this study was to analyze some of the known HT risk factors contributing to the variations between urban and rural areas of Turkey in HT development.Methods:We used data from the 2011 Chronic Diseases and Risk Factors Survey that was conducted by the Turkish Ministry of Health on a representative sample of the Turkish adult population aged 20 years or more (n=16.227). HT was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
3
21
0
2
Order By: Relevance
“…However, a small number of recent studies showed that the HTN prevalence was higher in rural areas than in urban ones. In Turkish adult population aged 20 years or more, the overall (age-standardized) prevalence of HTN was 24.9%, and was higher in rural (28.4%) than in urban areas (23.9%) 37 . Women were more likely to had HTN in rural areas than in urban areas (p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…However, a small number of recent studies showed that the HTN prevalence was higher in rural areas than in urban ones. In Turkish adult population aged 20 years or more, the overall (age-standardized) prevalence of HTN was 24.9%, and was higher in rural (28.4%) than in urban areas (23.9%) 37 . Women were more likely to had HTN in rural areas than in urban areas (p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…The Chinese Residents Nutrition and Chronic Disease Status Report (2015) [ 6 ] reported that the prevalence of hypertension among urban residents was 26.8% and among rural residents was 23.5%; the prevalence increased significantly with age for both urban and rural residents. The difference in prevalence of hypertension between urban and rural regions worldwide varies in both magnitude and direction [ 7 11 ]. In China, the difference in relative prevalence of hypertension in urban and rural regions has decreased, especially in the northern region [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension occurrence was higher in the UP for all survey years, and this prevalence was significantly associated with DCI. Dastan et al studied hypertension risk factor differences in rural and urban populations in 16,227 Turkish adults [36] and found urban living to be a risk factor for hypertension occurrence, with an odds ratio of 1.24 for men and 1.20 for women.…”
Section: Discussionmentioning
confidence: 99%